2011
DOI: 10.1021/jo201085r
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Phosphorus(V)-Mediated Nucleophilic Substitution Reactions: Development of a Catalytic Appel Reaction

Abstract: Catalytic phosphorus(V)-mediated chlorination and bromination reactions of alcohols have been developed. The new reactions constitute a catalytic version of the classical Appel halogenation reaction. In these new reactions oxalyl chloride is used as a consumable stoichiometric reagent to generate the halophosphonium salts responsible for halogenation from catalytic phosphine oxides. Thus, phosphine oxides have been transformed from stoichiometric waste products into catalysts and a new concept for catalytic ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
124
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(131 citation statements)
references
References 112 publications
6
124
0
1
Order By: Relevance
“…A very wide variety of all conceiveable reducing agents has been employed but none are problem-free. 1c Although hydride reagents have attracted some 20 recent attention, 2 at present silane reagents are the most commonly used, both in the laboratory and industrially. 4 A significant point in their favour is that, with care and with much process development, they can usually be made to stereospecifically reduce optically active phosphine oxides.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A very wide variety of all conceiveable reducing agents has been employed but none are problem-free. 1c Although hydride reagents have attracted some 20 recent attention, 2 at present silane reagents are the most commonly used, both in the laboratory and industrially. 4 A significant point in their favour is that, with care and with much process development, they can usually be made to stereospecifically reduce optically active phosphine oxides.…”
mentioning
confidence: 99%
“…13 We also studied an enantiomerically enriched P-stereogenic case, (S)-methylphenylo-tolylphosphine oxide (of 93% ee). 20 Disappointingly, this gave racemic phosphine borane under a variety of reaction conditions. 22 It was our strong suspicion that this racemisation was induced by the presence of the chloride counter ion of the chlorophosphonium salt.…”
mentioning
confidence: 99%
“…Two protocols for carrying out Appel reactions that are catalytic in phosphine oxide have been reported recently. 21,22,23 In the process of Denton and co-workers, oxalyl chloride reacts with the oxide to give chlorophosphonium 90 salt (vide infra), which in turn reacts with alcohol to give alkoxyphosphonium salt, resulting in alkyl chloride and regenerating phosphine oxide. Denton et.…”
mentioning
confidence: 99%
“…Denton and co-workers 21,22 have used a sequence 60 based on the treatment of phosphine oxide with oxalyl chloride as the basis for their catalytic Appel reactions. They reported that their protocol was less efficient for reactions involving secondary alcohols.…”
mentioning
confidence: 99%
“…Other notable synthetic procedures are the Mitsunobo reaction [3], the reaction of 2,4,6-trichloro- [1,3,5]-triazine (TCT) in DMF followed by addition of CH2Cl2 solution of the reactant alcohol [4], the reaction of alcohol with 2,3-trichloro-5,6-dicyanobenzo-quinone in the presence of triphenyl phosphine, CH2Cl2 and a phase transfer catalyst [5]. ROMP-gel supported triphenyl-phosphine [6], phosphorus(V) mediated nucleophilic substitution reaction [7] and finally the use of fluorous phosphine [8] besides others. The previously reported procedures suffer from the use of toxic and expensive reagents and further the use of triphenylphosphine makes product recovery difficult and time consuming specially due to the in situ formation of the phosphane oxide.…”
Section: Introductionmentioning
confidence: 99%